Effective Use of Interactive Methods in the Educational Process in Preschool Educational Organizations (Journal of Pedagogical Inventions and Practices, 2023)
In this article we will talk about the formation of children's communication with others, the means of communication, responsibility, self-criticism, a creative approach to solving problems, a correct and adequate assessment of their strengths. One of the main conditions for conducting lessons in a preschool educational institution is the use of interactive teaching methods and the activation of the mental activity of children at all stages of the lesson